Refashion, restyle, restitch : 20 stylish sewing projects from preloved clothes & homewares - Shore, Debbie (Writer on sewing); Hind, Kimberley (Search Press Limited, 2022)
"Upcycle unwanted clothes, and learn how to restitch them into 20 stylish home accessories and garments. Are you trying to cut down on clothing and fabric waste, but short on ideas of what to do with unwanted garments, bedsheets or curtains? In a brand-new collaboration between sewing superstar Debbie Shore and her dressmaker-blogger daughter, Kimberley Hind, here are 20 unexpected but amazingly practical, stunning ideas for upcycling and repurposing pre-loved fabrics to make accessories for both you and your home! Beginning with invaluable guidance on choosing your fabrics, as well as the essential notions and extras you'll need, discover a stunning, contemporary collection of projects to create using old garments and fabric around the house, or saved from thrift/charity stores: a boho-style lampshade made from an old dress; pillows made from men's shirts; a fabulous Mid-century handbag cut from pre-loved ladies' jackets; a chic shirt-sourced throw... There are a whole range of designs to sew and inspire you! Every project includes easy-to-follow instructions and illustrated step-by-steps. The variety of techniques used for the projects, such as English paper piecing, piping, fitting zips, dying and felting, are also explained clearly and with photographs, helping you create professional (and enviable) results. The beauty of working with pre-owned fabrics is that you won't get shrinkage or risk colour running, as these items will already have been laundered; you'll also have a fabulous choice of unique fabrics that you just wouldn't be able to buy new. And, of course, you're keeping that fabric from going into landfill! So be inspired to give it a go! Take a look in your wardrobe, salvage your old favourites and give them a new lease of life."--Amazon.com.